Sediment transport modelling in the upstream of Sungai Kuantan by using HEC-RAS - Nik Mohamed Zaki, Nik Mohd Nasir (2018)
Bukit Kenau Station is located in the upstream of Sungai Kuantan the state of Pahang where subjected to huge amount of rainfall during monsoon season that bring high impact sediment transport process. The river responses by increased or decreased sediment carrying capacity, changing in channel cross section, erosion and deposition along the channel, which impact on channel stability over a period of time. The study is to simulate the sediment transport around Sungai Kuantan (Kenau Station) by using one dimensional (1D) quasi unsteady flow HEC-RAS. There is few data required such as geometric data, hydrological data, temperature data and sediment data. The analysis is done by using Tofaletti method (suitable method) for various year of analysis which are one (1), three (3), five (5), and ten (10) year analysis. From the simulation and results, the river morphology of the riverbed can be forecast. The result also shows the location of erosion and deposition occurs. After ten (10) year simulation analysis, the maximum erosion occurs at the depth of 1.47 m at cross section of 44200 (4000 m from the downstream). Meanwhile, the maximum deposition about of 2.39 m height occurred at cross section of 40800 (600 m from the downstream). Therefore, the suitable location for mining activities is at cross section of 40800 (600 m from the downstream) since this location has high value of deposition. The main advantages of this study is the sediment transport can be forecast which it can give high impact to river channel stability and environmental issues around the river can be preserved.